Relaciones laborales entre las secretaria/os, directivos y jefes departamentales de las instituciones de Educación Media del cantón Latacunga, año 2014. - Molina Cela, Mayra Fernanda (2015)
This research work has as objective: to improve labor relations between the Secretarie, Departmental Directors and Heads of Institutions of Secondary Education of the Latacunga Canton, 2014, which improved the working relationship between the investigated parts, this plan contributes to work harmony, resulting in emotional stability of the employee and employer. The investigation allowed to identify the lack of communication between staff of the various institutions, which results labor relations and performance. The current study was developed to base on field research, libraries and websites, allowing feel the reality of the problem. That is therefore the improvement plan was carried out with the aim, to support people of the area of the Secretarial area and their respective leaders, helping the development of responsibilities and raising awareness on both sides to work together to achieve a satisfactory working environment through : strategies, techniques, tips and suggestions set out in this plan. The same will show the internal change to achieve it of course will be reflected throughout the institution, as internal problems also affect external customers.